THE INFLUENCE OF COMPETENCE, TEAMWORK, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT BANK ACEH SYARIAH IDI BRANCH - Nauval Putra; Ibrahim Qamarius; Yanita; Nurmala (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the influence of competence, teamwork, and work motivation on employee performance at Bank Aceh Syariah Idi Branch. The research was motivated by the strategic importance of human resources in Islamic banking, where employees are required to provide accurate, responsive, and Sharia-compliant services. A quantitative explanatory design was applied using a saturated sampling technique, involving all 83 employees as respondents. Primary data were collected through a structured Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 26. The findings show that competence, teamwork, and work motivation each have a positive and significant effect on employee performance. The regression model explains 85.2% of the variance in employee performance, while work motivation appears as the most dominant predictor. These results imply that employee performance in Islamic banking can be strengthened through integrated human resource strategies that combine competency development, collaborative team practices, and motivational systems based on recognition, career growth, and supportive work conditions.